Slipped Capital Femoral Epiphysis Associated With Athletic Activity. (May 2023) - Loder, Randall T.; Gunderson, Zachary J.; Sun, Seungyup; Liu, Raymond W.; Novais, Eduardo V.
Background: Little data exist regarding the association of slipped capital femoral epiphysis (SCFE) and sporting activities. Hypothesis: There is no association between SCFE and sporting activities. Study Design: Retrospective review of all SCFE cases at our institution from 2010 through March 2021. Level of Evidence: Level 3. Methods: All patients with idiopathic SCFE were reviewed looking for the presence/absence of sporting activities and symptom onset. Also collected were the age, symptom duration, and weight/height of the patient, sex, race, and stable/unstable nature of the SCFE. The severity of the SCFE was measured using the lateral epiphyseal-shaft angle. Results: There were 193 children (110 boys, 83 girls) with idiopathic SCFEs. The SCFE was stable in 147, unstable in 45, and unknown in 1. The average age was 12.1 ± 1.8 years, average SCFE angle 38° ± 20° and symptom duration 4.0 ± 5.1 months. An association with a sporting activity was present in 64 (33%). The sporting activity was basketball (18), football (11), baseball/softball (10), and others (23). Football, basketball, and soccer predominated in boys, baseball and running sports were equal between boys and girls, and cheerleading/gymnastics/dancing predominated in girls. Differences showed that those involved in sports had a slightly lower body mass index (BMI) (88th percentile vs 95th percentile, P = 0.00). There were no differences between those involved and those not those involved in sporting activities for symptom duration, SCFE severity, sex, race, or stable/unstable SCFE type. Conclusion: Sporting activities are associated with the onset of symptoms in 1 of 3 of patients with SCFE, refuting the null hypothesis. Clinical Relevance: A high level of suspicion for SCFE should be given when any peripubertal athlete presents with hip or knee pain regardless of BMI/obesity status, and appropriate imaging performed.